Desenvolvimento de um método reflectométrico ambientalmente mais amigável para a determinação de metoclopramida em formulações farmacêuticas - Doretto, Keity Margareth [UNESP]; Gotardo, Mara Andréia [UNESP]; Pezza, Helena Redigolo [UNESP]; Pezza, Leonardo [UNESP] (Sociedade Brasileira de Química, 2010)
A simple and more environmentally friendly method by combined spot test-diffuse reflectance spectroscopy for determining metoclopramide in pharmaceutical formulations is described. The method is based on the reaction between metoclopramide and p-dimethylaminocinnamaldehyde, in the presence of HCl, producing a colored compound (λmáx = 580 nm) on the filter paper. The linear range was from 5.65 x 10-4-6.21x10-3 mol L-1 (r = 0.999). The limit of detection was 1.27 x 10-4 mol L-1. The proposed reflectometric method was applied successfully to the determination of metoclopramide in pharmaceuticals and it was favorably compared with the Brazilian or British Pharmacopoeia methods at 95% confidence level.
Development of an environmentally more benign reflectometric method for the determination of metoclopramide in pharmaceutical formulations
Keywords: diffuse reflectance spectroscopy; metoclopramide; spot test